Influence of Composition and Ratio of Raw Materials on Suspension Property and Compressive Strength of Clay Grouting Material for Coal Mine Gob - Sun, Daosheng; Wang, Liang; Wang, Aiguo; Chen, Jiajia (Asian Journal of Chemistry, 2014)
The influence of the water-solid ratio, cement and lime dosage on suspension property and compressive strength for clay grouting material is investigated in this paper. The test results show that by increasing the water-solid ratio, the drainage rate of clay grout will be increased while the concretion rate of clay grout will be decreased. Adding the cement and lime, the drainage rate of grouts and the compressive strength will be increased and the concretion rate of grouts will be shortened. The compressive strength of clay-cement-lime grouts reaches to the peak when the lime dosage is 6 %. When the cement dosage is 12 %, the degree of increase is the largest for compressive strength of clay-cement-lime grouts and the strength is well-developed.